Calculus Learning Using an Epidemiological Influenza Mathematical Model Based on STEM to Enhance Mathematical Literacy Skills - Noprisa, Noprisa; Suryatul, Aini Asyhara (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Considering the growing importance of mathematical literacy in the 21st century, this study provides an initial insight into improving future STEM-based learning models in mathematics education. The research aims to describe students’ mathematical literacy skills as a foundation for enhancing STEM-oriented instruction in higher education. The participants were students of the Mathematics Education Study Program enrolled in a Calculus course at a university in Lampung, Indonesia. Data were collected through a mathematical literacy test and a student response questionnaire. Data were analyzed using an independent sample t-test to identify students’ strengths and weaknesses in mathematical literacy. The results show that students’ mathematical literacy remains low. The average score was 20.67, with nearly half of the students (46.67%) scoring below the mean. The highest achievement was found in the problem formulation indicator (57.78%), followed by reasoning (49.33%), interpretation and representation (46%), and application (38.33%) as the lowest. These findings suggest that students are relatively capable of formulating mathematical problems but struggle to interpret, represent, and apply them in real-life contexts. Overall, students tend to focus on procedural calculations rather than meaningful connections between mathematics and real situations. Therefore, STEM-based learning innovations are needed to strengthen conceptual understanding and problem-solving skills. The positive student responses indicate that the approach used in this study successfully fostered engagement, motivation, and deeper mathematical literacy.